2022
DOI: 10.5435/jaaosglobal-d-21-00105
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Dislocation of the Proximal Tibiofibular Joint: A Systematic Review and 10-year Experience From a Level 1 Trauma Center

Abstract: Introduction:Traumatic proximal tibiofibular joint dislocations occur infrequently and are typically the result of high-energy trauma. These injuries can be a marker of limb injury severity because patients often sustain vascular injury and are at high risk of amputation. The purpose of this study was to present a systematic review of traumatic proximal tibiofibular joint dislocations and compare rates of associated injuries with a retrospective series of patients at a level 1 trauma center. The secondary obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…A significant amount of force is often necessary to cause a dislocation of the PTFJ, and as such, PTFJ dislocations are often associated with other potentially distracting injuries, which may contribute to the relatively low rate of recognition and diagnosis. A systemic review by Rajan et al found that PTFJ dislocation had a high rate of associated open fractures (70.6%) -similar to the 76.7% rate found by , and preoperative peroneal nerve deficit (41.2%) (Rajan, Ramski, and Romeo 2022;Herzog, Serrano-Riera, and Sagi 2015), all of which are characteristic of high-energy, limb-threatening injury. The PTFJ dislocation in this case was consistent with an Ogden Type III dislocation, which occur in 10% of PTFJ dislocations and as stated above, are most often the result of direct trauma to the fibular head (Aladin, Lam, and Szypryt 2002;Ogden 1974b).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A significant amount of force is often necessary to cause a dislocation of the PTFJ, and as such, PTFJ dislocations are often associated with other potentially distracting injuries, which may contribute to the relatively low rate of recognition and diagnosis. A systemic review by Rajan et al found that PTFJ dislocation had a high rate of associated open fractures (70.6%) -similar to the 76.7% rate found by , and preoperative peroneal nerve deficit (41.2%) (Rajan, Ramski, and Romeo 2022;Herzog, Serrano-Riera, and Sagi 2015), all of which are characteristic of high-energy, limb-threatening injury. The PTFJ dislocation in this case was consistent with an Ogden Type III dislocation, which occur in 10% of PTFJ dislocations and as stated above, are most often the result of direct trauma to the fibular head (Aladin, Lam, and Szypryt 2002;Ogden 1974b).…”
Section: Introductionmentioning
confidence: 79%
“…This tension appeared to significantly relax after the PTFJ was manually reduced. Proper identification and protection of the nerve was done diligently, as there have been reports of postoperative common peroneal nerve palsy in patients preoperatively neurologically intact (Rajan, Ramski, and Romeo 2022).…”
Section: Click Here To Learn More About the Orthopaedic Implant Companymentioning
confidence: 99%
“…As a marker of severe limb trauma, the occurrence of PTFD may indicate the patient at higher risk of amputation [16]. However, reported amputation rate varies greatly in different studies [15,16,20].…”
Section: Discussionmentioning
confidence: 99%
“…As a marker of severe limb trauma, the occurrence of PTFD may indicate the patient at higher risk of amputation [16]. However, reported amputation rate varies greatly in different studies [15,16,20]. In a retrospective study of 30 patients with proximal tibiofibular dislocation by Herzog et al [15], only 2 patients underwent amputation due to a nonreconstructable extremity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation